Pengaruh Pola Asuh Orang Tua Terhadap Kedisiplinan Salat Siswa - Sari, Nia Rahma; Sulaiman, Sulaiman (Prodi Pendidikan Keagamaan Islam, 2025)
This study explores the influence of parenting styles on students’ discipline in performing daily prayers, focusing on eighth-grade students at SMP N 2 Pariaman. The research was motivated by the observed inconsistency in students’ prayer habits and the vital role of parental guidance in fostering religious discipline. The study aims to examine the dominant parenting styles, assess students’ prayer discipline, and analyze the correlation between the two variables. A quantitative approach was employed using a correlational design, with questionnaires as the primary data collection tool. The results reveal that authoritative parenting is more effective in encouraging prayer discipline, while permissive and authoritarian styles show weaker influence. Quantitatively, the influence of parenting style on prayer discipline was significant, with a regression coefficient of 0.273 and p < 0.05, indicating a positive relationship between the two variables. The study concludes that parenting style significantly affects students’ consistency in performing prayers, highlighting the need for balanced guidance and active parental involvement. These findings are expected to inform educators and parents in promoting better religious behavior among adolescents.